ADAPTASI MAHASISWA BARU TAHUN AKADEMIK 2004-2005 TERHADAP KEGIATAN BELAJAR PADA PROGRAM STUDI PENDIDIKAN GEOGRAFI FKIP UNISMA BEKASI - Hermanto . (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2005)
The research has a background of some obstacles found at the first semester students of Geography department, 2004/2005 Academic Year in adapting their teaming process. The number of students is 38 people; therefore it required solutions to overcome the problem. The research used the descriptive method and its questionnaire. The data analyses are done by using the cross table, highest percentage of it result is used in order to obtain the general aim. The first semester students should be able to adapt their self to their learning area, such their lecture, doing their assignment on time, and reading the references in a library. The lecturers as counselors are required to give support intensively in adapting their learning area